Evaluation of co-production in local government services (CO-PRO) - Siew, King Ting; Tze, Wee Lai; Engkamat, Adeline; Sze, Wei Yong (Universiti Teknologi MARA, Kedah, 2023)
Local government is often restricted by monetary and human capital resources in providing services. As a result, co-production becomes an important cost-effective method to deliver services to the public. In Sarawak, Padawan Municipal Council implements various initiatives and programs to improve the local economy and community empowerment through co-production, based on the theory of comparative advantage. To evaluate the effectiveness of the co-production method in delivering services, an innovative application called CO-PRO has been created to evaluate the co-production of local government services. The application is very useful and effective for all the stakeholders, who are involved in the co-production of local government services so that more services that match the needs and well-being of local community could be delivered and improved from time to time. In the CO-PRO, six aspects of co-production are evaluated namely: public innovation, individual well- being, citizen empowerment, efficiency and effectiveness, mobilization of resources and lastly democracy. The stakeholders could channel their talent, knowledge, skills, time, ideas, and feedbackin order to stimulate greater participation and support from the various community groups in local government coproduction initiatives and programs.